2015
DOI: 10.4314/tjpr.v14i3.26
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, Toxicological and Pharmacological Studies of <i>Asiasari Radix</i> et Rhizoma: A Review

Abstract: Herba Asari and Asiasari Radix (AR) have a centuries-old history as a folk medicine in AR, including antifungal, antimicrobial, antilisterial, antiallergic, acarcidal, larvicidal, anti-caries, anti-inflammatory, hepatoprotective, neuroprotective, cytotoxic and anticancer activities suggest its therapeutic potentials in drug discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Asiasari radix (AR) has long been used in traditional Korean and Chinese medicine to treat cough, toothache, headache, neuralgia, gingivitis, asthma, and allergies due to its anti-bacterial and analgesic effects [1]. Recently, the pharmacological roles of AR extracts (AREs) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Asiasari radix (AR) has long been used in traditional Korean and Chinese medicine to treat cough, toothache, headache, neuralgia, gingivitis, asthma, and allergies due to its anti-bacterial and analgesic effects [1]. Recently, the pharmacological roles of AR extracts (AREs) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 Previous studies have reported the chemical constituents of A. sieboldii, such as essential oils (eg, methyl eugenol, cineol, safrole, eucarvone, elemicin, and kakuol), lignans (eg, asarinin, xanthoxylol, and sesamin), and alkaloids (eg, aristolochic acid, aristolactam, and higenamine). [23][24][25] The contents of the compounds were compared between different collections of A. sieboldii using HPLC, ultra HPLC-quadrupole time-of-flight/mass spectrometry (MS), and gas chromatography (GC)-MS. 30,41,42 In addition, the contents of the essential oils of A. sieboldii were compared using GC according to the growth conditions and years of cultivation. 43,44 Other studies have proposed methods for the quantitative analysis of the components of A. sieboldii for quality control.…”
Section: Discussionmentioning
confidence: 99%
“…The major components of A. sieboldii are essential oil, lignans, and alkaloids, as reported in previous studies. 19,[23][24][25] The study of the components of traditional herbal medicines is very important to ensure the reliability of pharmacological and clinical research. 26 Because traditional herbal medicines have different chemical compositions, it is necessary to develop accurate and effective simultaneous quantification methods.…”
mentioning
confidence: 99%
“…Volatile oils, lignans, and alkamides are considered to be the major constituents related to the pharmacological activity of ARR [ 3 , 4 , 5 , 6 ]. During the past few years, several studies analyzing the volatile oils, lignans, and alkamides in ARR by gas chromatography–mass spectrometry (GC–MS) [ 7 ], high–performance liquid chromatography (HPLC) [ 8 ], and ultra–performance liquid chromatography (UPLC) [ 9 , 10 ] have been reported, and these constituents can be used as marker compounds for the quality control of ARR.…”
Section: Introductionmentioning
confidence: 99%